Null and void dismissal due to pregnancy and maternity - Arévalo Vela, Javier (2022)
This article explores the nullity of dismissal due to pregnancy or recent maternity within the Peruvian laws, considering the Peruvian legislation, case law and legal doctrine, as well as the International Labor Organization (ILO) Conventions.